ANALISIS GROUTING TEST, STUDI KASUS PERENCANAAN BANGUNAN GEDUNG PT. ASTRA OTOPARTS (PERSERO) TBK, KECAMATAN NGALIYAN, KOTA SEMARANG, JAWA TENGAH - Ricky Afrianda (Geological Engineering E-Journal, 2013)
Indonesia is a country that located at the confluence of three major plates, making itprone to ground movements disaster. PT. Astra Otoparts (limited) is a company thatset up branch office in semarang and located in areas that experiencing local massmovement (local). This happens because there is a slip plane, has a lithology thatconsits of soil embankment and clay that has low value of cohesion and poorconsistency. Therefore, it should be made ground investigation to determine howmuch strength and physical condition of the soil, so as to know the proper methods toovercome these problems.The method used is grouting, but before doing grouting, grouting experiments needsto be done, ie grouting test. Grouting test is a method that used to determine theeffectiveness of the grouting to be done.Based on the analysis that has been done, we can know that the grouting method canincrease the carrying capacity of the land on the foundation of the building. After themeasurement, the value of N-spt increase from 2 up to 19 in the CH-2 and in CH-1 upto 21 in depth 4.50m to 5.00m. In the depth 9.50m to 10.00m at each check bore holethe value of N-spt from the previous 16 - 21 up to more than 60 in each hole. In thedepth 14.50m to 15.00m at each check bore hole the value of N-spt increased fromthe previous 48 - 49 up to more than 60. Efforts to increase the value of SPT withgrouting method on soil that has a low bearing capacity at PT. Astra Otopartssuccessfully performed, so that the process of building PT. Astra Otoparts canproceed.